Praktik Social Responsibility pada Pedagang Muslim Kaki Lima: Perspektif Triple Bottom Line dan Nilai-Nilai Islam - Uswatun Hasanah; Tri Wahyu Oktavendi; Ihyaul Ulum (Jurnal Akuntansi Keuangan dan Bisnis, 2022)
The purpose of this study is to reveal the practice of Social Responsibility based on Islamic values. This study uses a qualitative-etnomedology approach with the unit of analysis is a Muslim Street Vendor. Depth interview is used for the data collection technique. The data analysis technique uses the stages of data reduction, data presentation, and verification. Muslim Street Vendors carry out Triple Bottom Line implementation, such as the profit from the sales of Muslim Street Vendors setting aside a portion of their profits for qurban. In terms of people, Muslim Street Vendors provide leftover food and also improve the welfare of their employees by providing incentives for every sale. Lastly, the planetary dimension is reflected in the activity of cleaning the surrounding outlets and disposing of garbage in its place, to maintain environmental sustainability. Islamic Values such as “ukhuwah” and gratitude are internalitation in implementation of SR. In other side, Spiritual Oriented also underlined in Implementation of SR., The implications of the practice of social responsibility seem small, but with the large number of street vendors, these small things can have a very big impact.